Evaluation of The Effect of Lack of Street Lights on Road User Safety: Case Study of Jalan Utama Kutamanggu Village - Cepy Prasetyo; Mohamad Taufik; Sri Anggraeni (Fakultas Teknik Sipil dan Perencanaan, 2025)
Majalengka is a city that lacks lighting, especially in Kutamanggu village. One of the most important factors in order to create safety and comfort in the transport environment is to improve the quality of road safetyn this day and age, time is no longer an obstacle for humans to do activities. There are many people who choose to utilise the night time as their time for activities. Street lighting is essential for the traffic system and for various social events. In the case of the main road in Kutamanggu village, there is no street lighting. Which makes motorists uncomfortable when passing through the road. This research examines the effects of insufficient street lighting on the road. Jalan Utama Kutamanggu Village on safety for road users, focusing on accident rates, traffic crime and public views on road safety. The research was conducted at Jalan Utama Kutamanggu Village, more precisely on the road Kutamanggu Village. This research employs a qualitative methodology incorporating perception analysis. The main data came from questionnaires given to 52 users Jalan Utama Kutamanggu Village. Respondents evaluated the importance and satisfaction of the existing street lighting on a 5-point scale, ranging from